Personalized Medicine in Ophthalmic Diseases: Challenges and Opportunities - Jin, Kai; Zhang, Chun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on personalized medicine in ophthalmic diseases, their challenges and opportunities, which often involves methods to achieve personalized diagnosis and treatment of ophthalmic diseases. Personalized medicine is a broadly used term to encompass approaches used to tailor healthcare to the needs of individual patients. It has been early adopted in ophthalmology and is mainly achieved through disease stratification and individualization. Therefore, diagnostic techniques that can realize comprehensive individual assessment are very important. Previous studies have put forward techniques such as next-generation sequencing and translational research. Gene therapy-based treatment trials have been presented for ophthalmic diseases such as retinitis pigmentosa and age-related macular degeneration. Recently, with the rapid development of artificial intelligence and interdisciplinary collaboration, concepts such as machine learning and wearable devices have been frequently discussed in ophthalmic research. There might be new promising methods to realize personalized ophthalmology.